Modeling Non-Cooperative Water Use in River Basins - Woldeyohanes, T.; Kuhn, A.; Heckelei, T.; Duguma, L.A. (MDPI, 2021)
Conventional water use and management models have mostly emulated purposefully designed water use systems where centralized governance and rule-based cooperation of agents are assumed. However, water use systems, whether actively governed or not, involve multiple, independent decision makers with diverse and often conflicting interests. In the absence of adequate water management institutions to effectively coordinate decision processes on water use, water users’ behaviors are rather likely to be non-cooperative, meaning that actions by individual users generate externalities and lead to sub-optimal water use efficiency. The objective of this review is to evaluate the advantages and disadvantages of recently proposed modeling systems dealing with non-cooperative water use regarding their ability to realistically represent the features of complex hydrological and socioeconomic processes and their tractability in terms of modeling tools and computational efficiency. For that purpose, we conducted a systematic review of 47 studies that address non-cooperative water use in decentralized modeling approaches. Even though such a decentralized approach should aim to model decisions by individual water users in non-cooperative water use, we find that most studies assumed the presence of a coordinating agency or market in their model. It also turns out that most of these models employed a solution procedure that sequentially solved independent economic decisions based on pre-defined conditions and heuristics, while only few modeling approaches offered simultaneous solution algorithms. We argue that this approach cannot adequately capture economic trade-offs in resource allocation, in contrast to models with simultaneous solution procedures.